CARBON EMISSION DISCLOSURE: A Study on Agriculture, Energy, and Industry Companies - Lulu Nofitasari; Rachmawati Resmilia; Siti Nur Hadiyati (Indonesian Journal of Advanced Research, 2024)
This study examines the factors that influence the disclosure of carbon emissions. The factors tested in this study include company size, profitability, competition, growth, debt-to-equity ratio, the reputation of a public accounting firm, and environmental performance. The method used to measure the extent of carbon emission disclosure adopts a checklist developed based on a request sheet obtained from the Carbon Disclosure Project (CDP). The sample of this study was selected using purposive sampling and selected 40 agriculture, Industry, and energy companies listed on the Indonesia Stock Exchange consecutively from 2020-2022. The results of this study indicate that profitability, growth, and reputation of public accounting firms have a significant effect on the disclosure of carbon emissions. In contrast, other factors have no significant effect.